Augmented Reality Pada Property Dengan Window Portal Depth Mask Shader - Ilmi, Alfiyani Nurul; Kaffi, Arrahman; Rizqi, Maulana (Majalah Ilmiah Teknologi Elektro, 2022)
The current home marketing strategy still uses social media accounts, brochures, and catalogs as promotional media. In the current use of promotional media, people are often confused about the shape of the house to be purchased, because the use of brochures as a promotional media that visualizes the shape of the house still using 2D makes a limited perspective, and the current situation is still the COVID-19 pandemic which makes it difficult for people to get out. home or out of the house. The need for an innovation that can visualize the shape of the house into a 3D object by using Augmented Reality technology. The purpose of this research is to produce an AR application that can be a marketing medium. Users just open the application and then point to the marker and the portal and 3D house will appear. The Augmented Reality application is tested to the public to measure the validity and feasibility as a marketing medium that has been filled out by respondents through Google Forms. For the development of the method using MDLC. The application of AR technology to applications produces Augmented Reality technology that can display houses in 3D through portals and can be an innovation for home marketing strategies to attract public interest. The results of application testing that have been carried out on AR application users obtained a percentage value of 88.6% with a very feasible category and can be used without revision.